Radiofrequency ablation of genicular nerve in a patient with knee pain associated with osteoarthritis - Mulyawan, Erwin; Prasetyadhi, Jokevin (DiscoverSys Inc., 2019)
ABSTRACTOsteoarthritis is a leading cause of pain and disability in the elderly. In addition to the economic burden, the pain caused by knee osteoarthritis may also reduce the quality of life and affect the patient's psychological condition. Surgery is the best option for patients with severe osteoarthritis. However, a patient with severe osteoarthritis generally tend to be elderly and have multiple co-morbidities, and thus, may not be a suitable candidate for surgery. In regards to several interventional methods that have been investigated, radiofrequency ablation (RFA) neurotomy showed promising results. We report a case of 65-year-old woman with chronic knee osteoarthritis pain that underwent a conventional RFA procedure for right genicular nerve.